2012
DOI: 10.1007/s00128-012-0666-z
|View full text |Cite
|
Sign up to set email alerts
|

Metals and Metalloids in the Water–Bloom-Forming Cyanobacteria and Ambient Water from Nanquan Coast of Taihu Lake, China

Abstract: Concentrations of 12 metal(oid)s were investigated in the bloom-forming cyanobacteria and ambient water samples collected monthly between March 2009 and February 2010 at the Nanquan coast of Taihu Lake, China. The metal(oid) concentrations in ambient water decreased in the order Fe > Zn > Ni ≈ As ≈ Cu > Mn > Ag > Cr > Se > Cd > Co > Tl, while those in cyanobacteria followed a sequence Fe > Mn > Zn > Cu ≈ Ni > Co > Ag > Cr ≈ As > Cd > Tl > Se. The metal(loid) burdens removed by cyanobacteria were estimated as 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…3D ). A previous studies conducted in the same sampling lake zone as our present study found that the concentrations of soluble metals in summer were much higher than in spring, such as iron increased from 24 ug/l in March to 86 ug/l in July (Su et al 2012 ), and soluble Cr increased from 40.90 to 114.70 ug/l (Fan et al 2019 ). There are likely two reasons for high concentrations of soluble heavy metals in summer in this lake area: one is that the DOC derived from Microcystis blooming can form complexes with metal ions; the higher concentration of Microcystis -blooming-derived DOC in summer thus leads to higher concentrations of soluble heavy metals (Fan et al 2019 ).…”
Section: Discussionsupporting
confidence: 65%
“…3D ). A previous studies conducted in the same sampling lake zone as our present study found that the concentrations of soluble metals in summer were much higher than in spring, such as iron increased from 24 ug/l in March to 86 ug/l in July (Su et al 2012 ), and soluble Cr increased from 40.90 to 114.70 ug/l (Fan et al 2019 ). There are likely two reasons for high concentrations of soluble heavy metals in summer in this lake area: one is that the DOC derived from Microcystis blooming can form complexes with metal ions; the higher concentration of Microcystis -blooming-derived DOC in summer thus leads to higher concentrations of soluble heavy metals (Fan et al 2019 ).…”
Section: Discussionsupporting
confidence: 65%
“…The possibility of using microorganisms in clean technologies for environmental decontamination has spurred the search for resistant organisms that are capable of biotransforming toxic elements such as As. Cyanobacteria are of interest because of their dominant position in aquatic environments impacted by different types of pollutants (Su et al 2012;Garcia-Meza et al 2005). Moreover, several studies have reported their ability to biotransform oxyanions of As into organic forms (e.g., Guo et al 2011;Yin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this study elements were selected according to Irving and Williams (1953) series stating that reactivity increases with atomic number being Cu the most reactive and Mn the less in the first transition series. Zinc shows a lower reactivity than Cu but higher than Mn (Su et al 2012). In addition, the studied elements may proceed from various anthropogenic and natural sources.…”
mentioning
confidence: 97%